2006
DOI: 10.1002/hed.20463
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis as a determinant of free flap utilization for reconstruction of the lateral mandibular defect

Abstract: Expectations of prognosis bias the surgeon's decision regarding flap selection. Reconstruction with a pectoralis flap does not necessarily contribute toward the desired outcome of reduced medical complications. Any functional comparison between reconstructive groups needs to account for those differences in health status and prognosis that might explain any observed postoperative differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Full‐text copies of 54 manuscripts were retrieved. Data was not retrieved from 37 of the 54 full‐text papers for meeting the following exclusion criteria; not using free flaps ( n = 2), not reporting a failure rate ( n = 7), using only 1 free flap harvest site ( n = 6), using an uncommon combination of free flaps ( n = 1), studying cadavers ( n = 1), studying animals ( n = 1), not reporting at least 1 failure ( n = 18), or containing data from another larger study ( n = 1) . Seventeen studies underwent data extraction and are reported in Table …”
Section: Resultsmentioning
confidence: 99%
“…Full‐text copies of 54 manuscripts were retrieved. Data was not retrieved from 37 of the 54 full‐text papers for meeting the following exclusion criteria; not using free flaps ( n = 2), not reporting a failure rate ( n = 7), using only 1 free flap harvest site ( n = 6), using an uncommon combination of free flaps ( n = 1), studying cadavers ( n = 1), studying animals ( n = 1), not reporting at least 1 failure ( n = 18), or containing data from another larger study ( n = 1) . Seventeen studies underwent data extraction and are reported in Table …”
Section: Resultsmentioning
confidence: 99%
“…There were 81 papers (16, 24, 29, 30, 31, 33, 38, 47, 49, 53, 55, 57, 63, 65, 66, 69, 71, 73, 75, 76, 81, 84, 89, 91, 95, 97, 99, 100, 103, 104, 107-109, 111-116, 120, 121, 124, 125, 130, 132-134, 137, 140 145-150, 154, 158, 163, 165, 166, 168, 170-173, 180, 184, 185, 188, 194-197, 202, 203, 205, 210, 212, 221, 222, 229) 98, 101, 106, 110, 110, 117-119, 122, 123, 126-129, 131, 135, 138, 139, 141, 143, 151, 153, 156, 159-161, 164, 167, 169, 179, 182, 183, 187, 190, 192, 193, 199, 200, 204, 206, 207, 209, 212, 214, 216, 218, 220, 223, 225, 227, 228) also reconstructed the condyle, compared with 1.6% (6/373) for the iliac crest (13,15,19,60,77,79,86,87,98,105,155,157,161,177,178,183,201,211,212,227 …”
Section: Classificationmentioning
confidence: 98%
“…9 In patients who may not be fit for extensive surgery involving free tissue transfer due to comorbidities, regional soft tissue flaps such as pedicled pectoralis major or cervicodeltopectoral can be used for reconstruction of L and H defects. In practice, it was found in a study by Deleyiannis et al 23,24 that advanced age (>70 years), moderate or severe comorbidity, and tumor involvement of the base of the tongue were factors that favored use of regional flaps.…”
Section: Type Of Defect and Approach To Reconstructionmentioning
confidence: 99%